(untitled) (Research, Society and Development, 2021)
The search for healthier and higher quality food, collected in natural environments and without the use of pesticides is the highlight of non-conventional food plants, thus gaining recognition for the ability to improve the quality of food for many rural and urban families. Non-conventional vegetables are those with limited distribution, restricted to certain locations, having great weight in the food and culture of traditional populations. In addition, they are species that are not organized as a production chain, not arousing commercial interest on the part of companies in the sector. Given the above, the objective of this work was to conduct field research with potential interest groups in PANC tracing their consumption profile and identify the PANC most commonly found in fairs of organic and agroecological products in the interior and capital of Alagoas. Field visits were made to the fairs in Maceió where there were reports of commercialization of PANCs and research with groups of potential interest in the theme of PANC: groups of consumers of organic and agroecological products, groups on the topic in social networks, and students of agroecology of the Maragogi / IFAL campus. All participants signed an informed consent form. The research with interest groups indicated that there is a target audience both for the commercialization of PANCs and also for educational products focused on this theme. There are several PANC options that could be commercialized by the residents of the settlements, either in natura or in processed products (adding value), thus being able to contribute to the family income.